Beyond bicentennial perspectives on Malays - Zainul Abidin bin Rasheed; Hussin Zoohri Wan 1937-; Norshahril Saat (World Scientific Publishing Co. Pte. Ltd., 2020)
The year 2019 marks Singapore's Bicentennial milestone since the arrival of Sir Stamford Raffles in Singapore in 1819. It was in anticipation of the arrival of the Bicentennial that this book, Beyond Bicentennial: perspectives on Malays, was initiated. This book is a collection of articles from prominent individuals and academicians that touch not only on the 200 years since the arrival of Raffles, but goes back 720 years earlier when Sang Nila Utama first set foot on the island in 1299.